The phenomenon of obesity and its relationship to the level of physical activity among secondary school students.( A study conducted between «Setif-Algeria and Afyon-Turkey ») - Daili, Imene; Bendjedou, Boutalbi (sports creativity, 2025)
This study aims to understand the relationship between obesity and the level of physical activity among high school students. The researcher used the descriptive method, considering it the appropriate approach, assisted by the Global Physical Activity Questionnaire (NAP) developed by Martin (2000) and personal interviews, alongside measuring and determining the Body Mass Index (BMI). The study sample included about 200 high school students, randomly selected from the state of Setif – Algeria, and Afyon – Turkey. When measuring the correlation between the level of physical activity (NAP) and the Body Mass Index (BMI) of these students, the researcher found a relationship linking the level of physical activity to obesity among high school students. Additionally, no statistically significant differences were observed in terms of gender and age regarding both the level of physical activity and the Body Mass Index between students from Setif – Algeria and students from Afyon – Turkey.